MODEL RISIKO PADA TAHAPAN PELAKSANAAN PEMBANGUNAN PROYEK BANGUNAN SWASTA YANG BERPENGARUH TERHADAP KINERJA PROYEK - Lepar, Frangky Ronald; Mandagi, Robert J. M.; Lumeno, Shirly S. (JURNAL SIPIL STATIK, 2018)
The successful implementation of construction projects can be seen from the accuracy of cost, time and quality. In an effort to control the potential risks need to be done risk identification comprehensively, in the analysis and then controlled, so it can reduce the opportunities and consequences of risks that will occur. The changes occurring in the project implementation phase then have an impact on the performance of the project, whether it be at the cost, quality, time and scope of work, which may pose a risk. As for the risk that there is something that can be tolerated by the owner so as to get additional costs or time and unisolable by the owner (non-excusable scope) so that all the consequences borne by the contractor. As for the purpose of this study is able to identify non-excusable change factors that have a dominant risk in the implementation phase of private building development projects in Manado which resulted in changes in project implementation performance, knowing the impact of any non-excusable change factor, and get the risk model generated from this research includes the mitigation of such risks.The research methodology used is to use quantitative method for data collection of the first stage which is analyzed by using SPSS, then qualitative method supported by survey and questionnaire for data collection stage 2 in analysis with SPSS. 23 is then used AHP (Analytic Hierarchy Process) method to determine the risk level.The results of the study aimed to obtain the non-excusable risks that are dominant in the implementation project of private building development in Manado city are as follows: 1) Using local workforce. 2) The owner likes to change to work image. 3) Many changes by the owner to the image. 4) Short execution time. 5) Morale and low work motivation.From the results of this study can be concluded that there are factors - scope non excusable change which has the risk of impacting changes in the performance of private construction projects in the city of Manado both in terms of cost performance, time, and quality. From the results of the study there are relationships (influence) risk factors that impact on changes in time and cost performance of private construction projects in Manado. The risk mitigation that must be made to mitigate the dominant negative risks in this study is one of the highest using local labor, by reducing the risk of recruiting known or known local laborers, coaching and briefing before work on targets and quality of work, awarding rewards to workers who meet the required criteria, making good contracts, evaluating work periodically, recruiting management personnel on reliable projects. May then transfer the risk or transfer the risk that will occur.Â Keywords: risk model, non excusable risk, private project performance